Disharmoni antara Praktik Adat dan Prinsip Syariat Islam: Studi atas Tradisi Mepahur di Desa Jongar, Aceh Tenggara - Altama, Yhogi; Agusman Damanik (Kartika: Jurnal Studi Keislaman, 2025)
This study examines the Mepahur tradition in Jongar Village, Southeast Aceh, as a cultural heritage of the Alas ethnic group, where young men and women meet through the exchange of poetic verses at night. While considered a respectful form of social interaction by the local community, the tradition has sparked debate due to concerns about its alignment with Islamic teachings, particularly regarding interactions between non-mahram individuals. This qualitative research involves observation, in-depth interviews with religious and traditional leaders, and a literature review of hadith texts. Findings reveal two dominant perspectives: some religious figures accept the tradition if conducted under supervision and within Islamic boundaries, while others view it as prohibited due to its potential for illicit interactions. Deviations from traditional norms were also found, contributing to the tension with religious principles. The study concludes that Mepahur can be preserved if reconstructed in accordance with Islamic values—by limiting interaction, ensuring gender separation, and maintaining oversight by community leaders. This highlights the importance of balancing cultural preservation with adherence to religious principles.